Release of aggregation pheromone by Tribolium castaneum (Coleoptera: Tenebrionidae): differences among geographic populations, biosynthetic mechanisms inferred by RNAi gene silencing, and neuroendocrine effects on production - Aikins, Michael Jamison (Kansas State University, 2024)
Intraspecific variation in pheromone release and response occurs commonly in many insect species. These variations could include differences in the isomeric composition of a given pheromone blend and the overall quantity produced. Feeding males of the red flour beetle, Tribolium castaneum (Coleoptera: Tenebrionsidae) produce an aggregation pheromone, 4,8-dimethyldecanal (DMD), that is attractive to both sexes. In this dissertation, I initially report the amount of aggregation pheromone released over 6-days by individual males from 14 populations of T. castaneum collected across North America, from Canada to Costa Rica. The populations studied also varied by their years in laboratory culture, from just one year for an Alabama population to over 50 yrs for a Kansas population. Pheromone released by single feeding males was obtained by headspace aeration and trapping the volatiles on the adsorbent Porapak-Q every 48 hrs for 6 days. Collected volatiles were eluted from the Porapak using hexane and analyzed by quantitative GC-MS. T. castaneum males produced varying amounts of DMD, from 1,547.5 ng for the Costa Rica population, to 99.3 ng for the Argyle, Manitoba population over a six-day period. Correlation analyses were done to examine any effects on pheromone release as a function of collection locality, years in colonization and morphometry of studied males for the pheromone data. Male body dimensions were measured from six populations and the amount of DMD produced was not significantly correlated with body length, width or area coverage for the beetles studied. The amount of DMD produced was not correlated with geographical location, the amount of time the populations have been cultured in the laboratory, or the size of the body regions measured. These findings are discussed in relation to previous studies that have quantified DMD from T. castaneum. Possible explanations for these differences are also explored. The biosynthetic pathway of DMD was investigated by performing RNA sequencing on ventral abdominal cuticles of T. castaneum. Several different analyses of the data along with literature clues provided 26 candidate genes. RNA interference (RNAi) was used to evaluate the effect of suppressing the targeted transcript on DMD production using the quantitative procedure described previously. Out of the 26 candidates 5 had a significant effect on the amount of DMD produced. Suppression of fatty acid synthase decreased DMD production to 2 % of that from non-injected controls. RNAi targeting a lipase-3-like protein and a putatitve fatty acyl-CoA reductase each reduced DMD production to that of 36 % and 55 % the amount produced by non-injected controls, respectively. Beetles injected with dsRNA targeting a previously identified and characterized desaturase, TcasZ9desA, and an unknown hypothetical protein each produced only 39 % the amount as non-injected controls. This information is used to discuss a possible biosynthetic route of DMD. Several neuroendocrine factors are known to affect pheromone production in several insect orders. Among these are juvenile hormone, its synthetic mimics, ecdysone and its derivatives. Adipokinetic hormone can mobilize an insect’s lipids storage indicating starvation, which in T. castnaeum prohibits DMD production. Biogenic amines can elicit a range of cellular responses and can orchestrate or modify physiological responses. Using the same system to collect and quantify DMD we tested these neuroendocrine factors ability to inhibit a feeding male from producing DMD, or to rescue a starved males inability to produce DMD. All of the compound tested, except dopamine, had no effect on DMD production in either fed or starved T. castaneum males. Dopamine showed an increase in the amount of DMD produced from feeding males but not statistically significantly more than control beetles. The results obtained here are discussed in the light of DMD production being under the influence of hormone or endocrine factors.
Keywords: Tribolium; RNA interference; Pheromones